ANALISIS PELAKSANAAN MENTORING KEROHANIAN ISLAM SEBAGAI SISTEM PEMBINAAN AKHLAK DI SMA NEGERI 1 BANYUASIN III KABUPATEN BANYUASIN - Amirunas Amirunas (Conciencia, 2017)
Education carried out as Islamic religious education that takes place in the classroom means that there has been an interaction process that leads to the achievement of the goals of education itself. Teachers and students interactively can provide meaning from education is a learning process by creating a conducive atmosphere, providing an environment and arousing enthusiasm in the learning process. The learning process carried out by teachers in the classroom is basically not only making students smart, but should instill educative values ​​in the act of educating them, so they can become complete human beings. To build a good and complete human being, every teacher should be able to do the learning process in front of the class properly and correctly according to the procedures outlined in the implementation of learning. After conducting teaching and learning activities the teacher certainly hopes to get the results of an effective and efficient teaching and learning process. Such as by teaching or fostering students by doing da'wah in a scientific assembly known as mentoring which is mentoring Islamic spirituality to familiarize students with purely Islamic teachings such as being accustomed to saying greetings when meeting with fellow Muslims, shaking hands, courtesy, mutual respect , Dhuha prayer, midnight prayer in congregation at school. Islamic spirituality mentoring activities carried out in SMA 1 Banyuasin III Banyuasin District is an activity of the science council, meaning that students join the assembly group among fellow students by carrying out educational activities which include teaching, educating, training, and fostering carried out by approach mutual advice advises.